A quaternion clustering framework - Piórek, Michał; Jabłoński, Bartosz (Zielona Góra: Uniwersytet Zielonogórski)
Data clustering is one of the most popular methods of data mining and cluster analysis. The goal of clustering algorithms is to partition a data set into a specific number of clusters for compressing or summarizing original values. There are a variety of clustering algorithms available in the related literature. However, the research on the clustering of data parametrized by unit quaternions, which are commonly used to represent 3D rotations, is limited.
Keywords: data clustering; quaternions data processing; human gait data processing